ChemInform Abstract: Magnetically Recoverable Catalyst for the Asymmetric Henry Reaction Based on a Substituted Imidazolidine‐4‐one Copper(II) Complex Supported by Fe3O4·SiO2 Nanoparticles. Issue 10 (February 2016) - Bhosale, Dattatry Shivajirao; Drabina, Pavel; Kincl, Miloslav; Vlcek, Milan; Sedlak, Milos
Abstract: A novel chiral heterogenous catalyst (FSCL) is prepared and successfully applied for the synthesis of nitroethanols (III) and the precursor (V) of the long‐acting β2 ‐adrenoreceptor agonist Salmeterol (VI).